NLRP3 inflammasome-dependent and -independent interleukin-1β release by macrophages exposed to wear and corrosion products from CoCrMo implants - Nasteho Abdoulkader; Jennifer Archibald; Morgane Lignereux; Eric A. Lehoux; Isabelle Catelas (PLoS ONE, 2025)
Wear particles and metal ions released from cobalt–chromium–molybdenum (CoCrMo) implants can trigger adverse local tissue reactions (ALTR) that can lead to implant failure. Identifying mechanisms involved in ALTR, particularly those underlying the initial inflammatory response elicited by wear particles (Cr 2 O 3 and CoCrMo) and metal ions (Co 2+ and Cr 3+ ) is therefore critical. The macrophage pro-inflammatory response to CoCrMo particles, Co 2+ , and Cr 3+ includes interleukin-1β (IL-1β) release, a process putatively linked to the NLPR3 inflammasome. However, the effects of Cr 2 O 3 particles remain largely unknown. The objectives of this study were to determine whether IL-1β release by macrophages exposed to Cr 2 O 3 particles (60 nm), CoCrMo particles (3.4 μm), Co 2+ , or Cr 3+ is dependent on NLRP3 and caspase-1, whether NLRP3-dependent release is mediated by reactive oxygen species (ROS) and/or cathepsin B, and whether caspase-8 is involved when the release is NLRP3 independent. Bone marrow-derived macrophages (BMDM) from wild-type ( wt ), NLRP3-deficient ( Nlrp3 -/- ), and caspase-1-deficient ( Casp1 -/- ) mice were exposed to the particles or metal ions following priming with lipopolysaccharide. IL-1β release induced by Cr 2 O 3 particles and Cr 3+ was shown to be both NLRP3 and caspase-1-dependent. In contrast, IL-1β release induced by CoCrMo particles and Co 2+ occurred independently of NLRP3, being caspase-1-independent in response to CoCrMo particles and partially caspase-1-dependent in response to Co 2+ . Further analysis suggested that NLRP3 inflammasome activation by Cr 2 O 3 particles was cathepsin B dependent and mediated by lysosomal destabilization, whereas activation by Cr 3+ was ROS-mediated. NLRP3-independent IL-1β release induced by CoCrMo particles or Co 2+ was caspase-8 dependent. Collectively, these findings highlight the diversity and specificity of the mechanisms by which different CoCrMo implant wear particles and metal ions can induce IL-1β release in macrophages. Moreover, they suggest that targeting NLRP3, caspase-1, and/or caspase-8 could help mitigate the IL-1β-mediated component of the inflammatory response triggered by wear particles and metal ions from CoCrMo implants.